Chromosome (re)positioning in spermatozoa of fathers and sons - carriers of reciprocal chromosome translocation (RCT) - Marta Olszewska; Ewa Wiland; Nataliya Huleyuk; Monika Fraczek; Alina T. Midro; Danuta Zastavna; Maciej Kurpisz (BMC, 2019)
Abstract Background Non-random chromosome positioning has been observed in the nuclei of several different tissue types, including human spermatozoa. The nuclear arrangement of chromosomes can be altered in men with decreased semen parameters or increased DNA fragmentation and in males with chromosomal numerical or structural aberrations. An aim of this study was to determine whether and how the positioning of nine chromosome centromeres was (re)arranged in the spermatozoa of fathers and sons - carriers of the same reciprocal chromosome translocation (RCT). Methods Fluorescence in situ hybridization (FISH) was applied to analyse the positioning of sperm chromosomes in a group of 13 carriers of 11 RCTs, including two familial RCT cases: t(4;5) and t(7;10), followed by analysis of eight control individuals. Additionally, sperm chromatin integrity was evaluated using TUNEL and Aniline Blue techniques. Results In the analysed familial RCT cases, repositioning of the chromosomes occurred in a similar way when compared to the data generated in healthy controls, even if some differences between father and son were further observed. These differences might have arisen from various statuses of sperm chromatin disintegration. Conclusions Nuclear topology appears as another aspect of epigenetic genomic regulation that may influence DNA functioning. We have re-documented that chromosomal positioning is defined in control males and that a particular RCT is reflected in the individual pattern of chromosomal topology. The present study examining the collected RCT group, including two familial cases, additionally showed that chromosomal factors (karyotype and hyperhaploidy) have superior effects, strongly influencing the chromosomal topology, when confronted with sperm chromatin integrity components (DNA fragmentation or chromatin deprotamination).